1436. Risk Factors for Invasive Pneumococcal Disease in Adults ≥65 Years Old Following Pneumococcal Conjugate Vaccine Recommendation. (26th November 2018) - Almendares, Olivia M; Xing, Wei; Farley, Monica M; Schaffner, William; Thomas, Ann; Reingold, Arthur; Harrison, Lee H; Holtzman, Corinne; Rowlands, Jemma V; Petit, Susan; Barnes, Meghan; Torres, Salina; et al.
Abstract: Background: In 2014, pneumococcal conjugate (PCV13) and polysaccharide (PPSV23) vaccines were recommended in series for all US adults ≥65 years. We conducted a case–control study to evaluate risk factors for invasive pneumococcal disease (IPD) among adults ≥65 years old. Methods: IPD cases (isolation of pneumococcus from sterile sites) were identified through Active Bacterial Core surveillance during 2015–2018. Isolates were serotyped using whole genome sequencing. Four controls, identified through a commercial database, were matched per case by age and zip code. We obtained vaccination and medical histories from providers, vaccine registries and participant interviews. A functional status score was calculated based on participant interview. We calculated IPD odds ratios using multivariable conditional logistic regression. Results: We enrolled 328 IPD cases and 1, 280 matched controls. Fifty percent of case-patients and 55% of controls received a dose of PCV13. Case-patients were more likely than controls to have a chronic condition (heart, liver, or lung disease, diabetes, cochlear implant, alcohol abuse, smoking; 82% vs. 59%), immunosuppression (60% vs. 32%), poor functional status (score of ≥ 3; 71% vs. 50%), annual household income < 30, 000 (38% vs. 25%) and education level of high school or less (36% vs. 25%). In a multivariable model, case-patients were more likely than controls to have a chronic condition (OR 2.48, 95% CI 1.72, 3.58), immunosuppression (OR 2.56, 95% CI 1.92, 3.42), poor functional status (OR 3.66, 95% CI 2.42, 5.54), and primary or secondary smoking exposure (OR 3.09, 95% CI 1.32, 7.2). In analysis limited to PCV13-type cases and matched controls, adjusting for PCV13 receipt, measures of association were no longer significant for chronic conditions (OR 1.45, 95% 0.71, 2.95), immunosuppression (OR 1.51, 95% CI 0.83, 2.74), or poor functional status (OR 1.98, 95% CI 0.91, 4.3). Conclusion: Chronic and immunosuppressive conditions remain IPD risk factors for adults in the era of PCV13 use; poor functional status was also identified as a risk factor. Targeted evaluation of adults with poor functional status could inform IPD prevention strategies. PCV13 may reduce the risk of PCV13-type IPD associated with chronic conditions and poor functional status. Disclosures: W. Schaffner, Merck: Member, Data Safety Monitoring Board, Consulting fee; Pfizer: Member, Data Safety Monitoring Board, Consulting fee Dynavax: Consultant, Consulting fee; Seqirus: Consultant, Consulting fee; SutroVax: Consultant, Consulting fee; Shionogi: Consultant, Consulting fee.